Observations on Cardiac Arrythmias during Laparoscopy - Scott, D. B. (1972)
The incidence of cardiac arrhythmias occurring during laparoscopy was studied in 100 consecutive patients who received carbon dioxide to inflate the abdomen and compared with that in 45 patients in whom nitrous oxide was substituted for carbon dioxide. Seventeen patients receiving carbon dioxide and two receiving nitrous oxide developed multiple arrhythmias, the commonest variety being fusion beats due to ventricular ectopic beats. Blood gas determinations showed that carbon dioxide caused a significantly higher level of Paco(2) and a lower pH than did nitrous oxide.